The Role of Islamic Philanthropy in the Orphans' Socio-Economic Development Based on Maqashid Sharia (Case Study in the Gerakan Infaq Beras Bandung) - Kakah Mudrikah; A Jajang w Mahri; Aas Nurasyiah (Review of Islamic Economics and Finance (RIEF), 2020)
This research departs from the many most vulnerable strata of society, one of which is children victims of neglect by their families and surrounding communities. Based on facts on the ground, in 2016, there were 5.3 million more children who were victims in the community. To protect the child, institutions such as an orphanage are needed to be a decent place to live, provide affection, and meet the basic needs of neglected children well. This research measure and describe the orphans socio-economic development using sharia maqashid principles. The objects taken in this study are orphans who live in orphanages in the Bandung Raya area (Bandung City, Bandung Regency, West Bandung Regency, and Cimahi City) who are receiving assistance from Islamic philanthropy distributed through the Gerakan Infaq Beras Bandung totaling 93 foster children. Through this Islamic philanthropy, it is also expected that the basic needs of orphans based on the principles of sharia maqashid can be met even better. The five dimensions of the principle of maqashid sharia, namely health services, access to education, religious practices, carrying out economic activities, and inclusion in social activities are operationally measured using the Maqashid Sharia Multidimensional Poverty Index (MSMPI). The research findings show that the socio-economic conditions of orphans in the health, education, religion and social variables get better towards a positive direction. In contrast, the socio-economic development of the economic variable gets a negative change. But in the aggregate, the orphans socio-economic development reflected in the MSMPI score gets a value of 3.54, which means that Islamic philanthropy plays a positive role in the orphans socio-economic development in the Bandung Raya area.